Asignación de rutas de vehículos para un sistema de recolección de residuos sólidos en la acera - Ayala Rodríguez, Alexander; Gonzáles Butrón, Edgar (Revista de Ingeniería, 2001)
Solid waste collection problems are of increasing concern to expanding cities and sectors with high volumes of waste generation. This paper deals with the optimization of a collection system in the sidewalk for urban sectors. This is a combinatorial problem in which all arcs of a mixed network are traversed, subject to vehicle capacity and time restrictions. A flexible formulation is proposed which works with separate collection and transportation networks. A sequencing scheme to assign routes is also proposed. The performance of the model is analyzed under different scenarios and applied to a collection zone of Bogotá with satisfactory results.